2017
DOI: 10.1186/s12889-017-4615-y
|View full text |Cite|
|
Sign up to set email alerts
|

Geographic Variations and Time Trends in Cancer Treatments in Taiwan

Abstract: BackgroundTargeted therapies have become important treatment options for cancer care in many countries. This study aimed to examine recent trends in utilization of antineoplastic drugs, particularly the use of targeted therapies for treatment of cancer, by geographic region in Taiwan (northern, midwestern, southern, and eastern regions and the outer islands).MethodsThis was a retrospective observational study of antineoplastic agents using 2009-2012 quarterly claims data from Taiwan’s National Health Insurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This study aimed to take the first step towards identifying the capacity for saving health resources in oncology care. To our knowledge, this is the first study to determine the association between the proportion of hospitalisation for inpatient chemo/radiotherapy treatment and staffed hospital beds per capita [17]. While a previous study described the regional variation in the proportion of chemotherapy cases in Taiwan, it did not examine the association between the proportion of chemo/radiotherapy cases and health resources [17].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This study aimed to take the first step towards identifying the capacity for saving health resources in oncology care. To our knowledge, this is the first study to determine the association between the proportion of hospitalisation for inpatient chemo/radiotherapy treatment and staffed hospital beds per capita [17]. While a previous study described the regional variation in the proportion of chemotherapy cases in Taiwan, it did not examine the association between the proportion of chemo/radiotherapy cases and health resources [17].…”
Section: Discussionmentioning
confidence: 92%
“…To our knowledge, this is the first study to determine the association between the proportion of hospitalisation for inpatient chemo/radiotherapy treatment and staffed hospital beds per capita [17]. While a previous study described the regional variation in the proportion of chemotherapy cases in Taiwan, it did not examine the association between the proportion of chemo/radiotherapy cases and health resources [17]. Consistent with previous studies in other fields [9], our study revealed a positive association between the number of hospital beds and the proportion of hospitalisation for inpatient chemo/radiotherapy treatment for breast cancer, which extends the findings of the Taiwanese chemotherapy study.…”
Section: Discussionmentioning
confidence: 99%